2007
DOI: 10.1002/term.36
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis at the development phase of a potential health technology: examples based on tissue engineering of bladder and urethra

Abstract: The Headroom Method can help inform instrumental decisions concerning new treatments without having to build a complex model with very wide parameter uncertainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 45 publications
1
60
0
Order By: Relevance
“…Not surprisingly, the new bioreactor-based approach also carries certain weaknesses and invokes threats that need to be addressed as part of a well developed clinical, regulatory and reimbursement plan. In order to derive more quantitative indications, the use of a Headroom Method has been proposed as a simple but rigorous way to make preliminary conclusions as to the cost-effectiveness of a new tissue engineering treatment [22].…”
Section: Commercial Aspectsmentioning
confidence: 99%
“…Not surprisingly, the new bioreactor-based approach also carries certain weaknesses and invokes threats that need to be addressed as part of a well developed clinical, regulatory and reimbursement plan. In order to derive more quantitative indications, the use of a Headroom Method has been proposed as a simple but rigorous way to make preliminary conclusions as to the cost-effectiveness of a new tissue engineering treatment [22].…”
Section: Commercial Aspectsmentioning
confidence: 99%
“…Several studies identified early models as useful tools to inform device development programmes, including early market assessment, research and development (R&D) portfolio management, and first estimations of pricing and reimbursement scenarios [83][84][85][86]. Two studies provided applied examples of using modelling to inform value [37,84].…”
Section: Early Modelsmentioning
confidence: 98%
“…Two studies provided applied examples of using modelling to inform value [37,84]. Two studies recommended using a Bayesian approach to incorporate all available evidence to help companies manage uncertainties and identify major risks and hence make better informed choices at each decision point [76,87].…”
Section: Early Modelsmentioning
confidence: 98%
“…More detailed accounts of this work can be found in McAteer et al . 4 It can be seen from these examples that health gain in Box 1: Regenerative medicine for urethral stricture A substitute for urethral tissue is needed in operations on lengthy strictures, and sometimes for epispadias and hypospadias (congenital defects resulting in the urethral opening on the top or bottom surface of the penis). Buccal mucosa, tissue making up the lining of the cheek, is becoming the gold standard substitute, 14 although it does have disadvantages, relating to morbidity at the donor site.…”
Section: Estimating Qalymentioning
confidence: 98%
“…For example, it curtailed. 4 Return on investment may be affected by the rarity of a condition or because it occurs only in economies unable to support high-cost remedies. For example, a tissue-engineered solution to small contracted bladders could not rely on treating Bilharziasis patients, since this parasitic disease occurs mostly in the world ' s poorest countries.…”
Section: Refi Ning the Clinical Problemmentioning
confidence: 99%